Factorial Invariance of the Maslach Burnout Inventory Student Survey (MBI-SS) in Chilean and Spanish University Students - Valdés Castro, María Pía (2023)
Introduction: The Maslach Burnout Inventory-Student Survey (MBI SS) is one of the most recognized instruments worldwide to assess burnout in the student population. Objective: To estimate the psychometric properties of the Maslach Burnout Inventory Student Survey (MBI-SS) in Chilean and Spanish university students. Method: An instrumental study was carried out in a non-probabilistic sample by quotas in 103 Chilean university students and 104 Spanish students. A confirmatory factorial analysis was performed, the reliability of the instrument and its factorial invariance for the Spanish and Chilean samples were analyzed. Results: The results confirm its three-factor factor structure and show that the instrument has adequate reliability and factor invariance in its proposed 12-item version. Discussion: It is concluded that this instrument and its psychometric properties allow the evaluation of academic burnout in Chilean and Spanish students.